2019
DOI: 10.1039/c8cy02033g
|View full text |Cite
|
Sign up to set email alerts
|

Rare-earth ion exchanged Cu-SSZ-13 zeolite from organotemplate-free synthesis with enhanced hydrothermal stability in NH3-SCR of NOx

Abstract: Rare-earth Y exchanged Al-rich Cu-CHA shows significantly improved hydrothermal stability in NH3-SCR reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
73
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 43 publications
5
73
0
Order By: Relevance
“…Usui et al [5] demonstrated that introduction of a small amount of Ce by wet and solid-state ion-exchange routes could improve SCR activities over a broad temperature range, because it enabled abundant Brønsted acidity sites and stabilized the framework of SSZ-13. The results of Zhao et al [6] also confirmed that rare earth ions (Ce 3+ , La 3+ , Sm 3+ , Y 3+ , Yb 3+ ) that modified Al-rich Cu-SSZ-13 catalysts had no significant impact on low-temperature NO conversions in the fresh catalyst but displayed enhancement of low temperature activity after hydrothermal aging when compared with Cu-SSZ-13. Similarly, Wang et al [7] reported that Ce or Sm could be introduced into Cu-SSZ-13 by ion exchanged preparation procedures, and the counterparts were investigated in detail.…”
Section: Introductionmentioning
confidence: 79%
“…Usui et al [5] demonstrated that introduction of a small amount of Ce by wet and solid-state ion-exchange routes could improve SCR activities over a broad temperature range, because it enabled abundant Brønsted acidity sites and stabilized the framework of SSZ-13. The results of Zhao et al [6] also confirmed that rare earth ions (Ce 3+ , La 3+ , Sm 3+ , Y 3+ , Yb 3+ ) that modified Al-rich Cu-SSZ-13 catalysts had no significant impact on low-temperature NO conversions in the fresh catalyst but displayed enhancement of low temperature activity after hydrothermal aging when compared with Cu-SSZ-13. Similarly, Wang et al [7] reported that Ce or Sm could be introduced into Cu-SSZ-13 by ion exchanged preparation procedures, and the counterparts were investigated in detail.…”
Section: Introductionmentioning
confidence: 79%
“…The stabilization effect of the introduction of rare earth cations into small pore zeolites has been less explored probably because of the limited diffusion of the relatively large hydrated rare earth ions through the 8R windows. The incorporation of Ce, La, Sm, Y and Yb into the Cu-SSZ-13 zeolites has been reported to enhance the framework stability aer hydrothermal aging at 800 C. 161,163,167,168 163 reported the incorporation of Ce 3+ cations to stabilize the Al in framework positions in the zeolite Cu-SSZ-13 aer hydrothermal treatment at 800 C for 20 h; moreover, the H 2 -TPR results suggested that the Cu 2+ cations in the aged Ce-containing samples are mainly located in the 6R, suggesting that the presence of Ce prevents the migration of Cu 2+ during the steaming treatment.…”
Section: Rare Earth and Alkaline Cations The Incorporation Of Extra-framework Cations Has Been Proven As An Efficientmentioning
confidence: 99%
“…Zhao et al 168 studied the effect of incorporation of several rare earth cations (Ce, La, Sm, Y, and Yb), finding that Y 3+ cations led an enhancement of the hydrothermal stability and catalytic performance of Cu–CHA in the NH 3 –SCR reaction. However, an excess of Y 3+ causes difficulties in the incorporation and diffusion of Cu 2+ cations and reduces the activity of the catalyst at low temperatures in the SCR reaction.…”
Section: Improvement Of Hydrothermal Stability By the Introduction Of Extra-framework Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Catalysts were the core part of SCR reaction, various catalysts have been developed, such as manganese-based catalyst, [5][6][7][8] vanadium-based catalyst, [9][10][11][12] rare earth-based catalyst, [13,14] carbon-based catalyst, [15][16][17] etc. Among them, cerium-based catalysts have gradually become a research hotspot because of the great performance and wide temperature windows.…”
Section: Introductionmentioning
confidence: 99%